(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Lillo EP, Malaki AB, Alcazar SMT, Rosales R, Redoblado BR, Diaz JLB, Pantinople EM, Buot Jr. IE. 2021. Inventory of native and mother trees in Key Biodiversity Areas of Cebu Island, Philippines for species selection in local reforestation programs. Biodiversitas 22: 4740-4749. Forest restoration is the counterforce of deforestation and forest degradation. Yet, despite promoting natural recovery after forest harvest, afforestation and reforestation efforts, tropical forest ecosystems still experience a poor ratio of forest loss to forest gain. The study assessed the native tree species and potential mother trees in different Cebu Island Key Biodiversity Areas (KBAs) as well as their distribution and habitat preferences which can be used in local reforestation programs. A vegetation survey was conducted in three KBAs in Cebu Island, namely Nug-as forest, Mount Lantoy and Mount Capayas to inventory all native species. Assessment based on the phenotypic characteristics of adult trees was also conducted for indicating mother trees. This study in Cebu Island KBAs recorded a total of 292 species, categorized into 125 families and 203 genera, which can be classified into native trees (210), vines and lianas (18), shrub (37), and herbs (27). Out of the 292 species, 214 were recorded in Nug-as forest, 172 in Mount Lantoy, and 145 in Mount Capayas. Of the 210 native tree species, Nug-as forest had 145 species, Mount Lantoy 131 species, and Mount Capayas 109 species. A total of 241 mother trees were identified in the three KBAs, corresponding to 77 species in which Nug-as forest had 143 trees correspond to 52 species, Mount Lantoy had 68 trees correspond to 29 species, and Mount Capayas had 31 trees correspond to 6 species. Such native tree species are recommended for reforestation programs as planting materials that could reduce the risks of failure due to its high adaptability to the environment.